SAT0633-HPR Social Support May Be Important for Improving Patient Satisfaction and Health Status in Patients with Rheumatoid Arthritis Treated with Biologics. (15th July 2016) - Fusama, M.; Yukioka, K.; Kuroiwa, T.; Yukioka, C.; Inoue, M.; Higashi, K.; Ogata, A.; Murata, N.; Kuritani, T.; Maeda, K.; Sano, H.; Yukioka, M.; et al.
Abstract : Background: The clinical benefits of biologics to patients with rheumatoid arthritis (RA) have been demonstrated in various clinical trials. However, patient satisfaction in patients treated with biologics is not well evaluated. Objectives: We evaluated patient satisfaction and health status in patients with RA treated with biologics. Methods: The patients with RA who were planning to be treated with IL-6 inhibitor (tocilizumab; TCZ) (IL-6 group) and TNF inhibitor (adalimumab: ADA, infliximab; IFX, etanercept; ETN) (TNF group) were enrolled. Disease activity was evaluated using swollen joint counts (SJC), tender joint counts (TJC) and patient global assessment (PGA), and Clinical Disease Activity Index (CDAI). Patient satisfaction was evaluated utilizing patient satisfaction scores of the Arthritis Impact Measurement Scale 2 (AIMS-2). Satisfaction was measured before and after 6-months of treatment with each of the biologics, and the results were compared. Statistical analysis was performed utilizing Wilcoxon rank-sum test and t-test. Results: Patients with RA (n=85) were evaluated in this study. 48 patients were treated with TCZ, and 47 patients were treated with anti-TNF agents (ADA: 17, IFX:17, ETN:13).Patients characteristics were as follows as follows: mean±SD of age (55.6±11.9 years old) and duration (7.29±8.83 years), male/female (16/79). Both at baseline and at 6 months after treatment, there was no statistically significant differences in SJC, TJC, PGA, EGA and CDAI between TCZ group and TNF group. All these evaluations showed statistically significant improvement after 6 months of treatment in each group.As for health status, all 5 components of AIMS-2 showed statistically significant improvement at 6 months compared to the baseline in TNF groups. In IL-6 group, "physical", "symptom", "affect" and "role" improved significantly at 6 months (p<0.001, for all items), while "social interaction" did not statistically improve compared to the baseline (p=0.114). Out of 12 satisfaction scores, all scores except "understanding and support for patients' problems by families or friends" (p=0.133) showed statistically significant improvement with 6 months of treatment in TNF group, while all 12 scores improved significantly at 6 months in IL-6 groups. Conclusions: Patient satisfaction and health status except social interaction were improved by TNF inhibitor or IL-6 inhibitor. To solve the problems related to social function, understandings and social support for patients by health professionals may be required. Disclosure of Interest: None declared